Exploring the Contextual Factors of Religious Leader Participation in Health Communication: Evidence from a Qualitative Study in Sierra Leone - Luetke Lanfer, Hanna (Journal of religion and health, 2023)
As there are many and sometimes ambivalent intersections of health and religion, strategic collaborations with religious opinion leaders in health campaigns have been increasingly explored. Despite the known influence of distinct contextual factors within emergency and non-emergency settings, existing research seldom distinguishes between those different factors and their impact on the inclusion of religious leaders as health messengers. To compare the contextual factors of religious leaders as health messengers during emergency and non-emergency situations in a setting with high religious affiliations, this study used a qualitative approach and triangulated the perspectives of three different samples, including (religious) opinion leaders, members of religious communities, and developers of health communication strategies in Sierra Leone. The results provide multifaceted insights into contextual factors applicable to emergency and non-emergency settings as well as the risks and opportunities. Recommendations for the incorporation of religious leaders in health promotion activities in consideration of different contextual factors are provided.